The evolution of inpatient treatment in hospitals with and without the presence of a Dental Surgeon: Comparison in two cities in Minas Gerais (Research, Society and Development, 2023)
The contribution of the dental surgeon to a multidisciplinary team results in helping the hospitalized patient recover. Oral health hold by the dental surgeon (DS) reduces significantly the appearance of diseases related to breathing and the proliferation of bacteria in other vital organs. This work's goal is to present the importance of DS in the recovery of patients admitted to hospitals and to compare the evolution of patients admitted to hospitals with and without the role of the dental surgeon in the multidisciplinary team. So it is concluded that the inclusion of the dental surgeon in the multidisciplinary team reduces the length of hospital stay for patients, it reduces hospital and patient's expenses as well, and it also increases the field for the newly graduated student.